2003
DOI: 10.1021/ja029645k
|View full text |Cite
|
Sign up to set email alerts
|

The C-Glycosyltransferase UrdGT2 Is Unselective toward d- and l-Configured Nucleotide-Bound Rhodinoses

Abstract: UrdGT2 is a d-olivosyltransferase from the metabolic pathway of urdamycin A, an angucycline antitumor and antimicrobial drug. The remarkable feature of this biocatalyst is its ability to set up C-glycosidic bonds. Using an in vivo system suitable to deliver the trideoxysugar rhodinose in both d- and l- configuration we could verify that both have been accepted as substrates and attached to the urdamycin polyketide backbone via a C-glycosidic bond. Regardless of the stereochemistry, these C-glycosides served as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 20 publications
(20 reference statements)
2
57
0
2
Order By: Relevance
“…Only a few C-GTs involved in the biosynthesis of natural products have been characterized so far, such as, the pathogen-associated C-GT IroB [31] or UrdGT2. [16][17][18] C-Glycosylated products are of particular interest as they are stable against glycosidase degradation. [32] We resequenced the putative gilGT gene which was believed to encode the C-GT involved in the biosynthesis of GV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few C-GTs involved in the biosynthesis of natural products have been characterized so far, such as, the pathogen-associated C-GT IroB [31] or UrdGT2. [16][17][18] C-Glycosylated products are of particular interest as they are stable against glycosidase degradation. [32] We resequenced the putative gilGT gene which was believed to encode the C-GT involved in the biosynthesis of GV.…”
Section: Discussionmentioning
confidence: 99%
“…The highest homologies were found with LanGT2 (38% amino-acid identity), a GT presumed to be involved in attaching the first D-olivose to landomycin aglycon, [13][14][15] and UrdGT2 (31% amino-acid identity), which is the C-GT of the urdamycin biosynthetic pathway. [16][17][18] The previously reported putative GilGT protein had 495 amino acids, which is approximately 120 amino acids longer than any other polyketide GT found so far. [11] Because several attempts to generate a gilGT mutant by in-frame deletion failed (data not shown), we resequenced the entire region of the gene cluster and found a sequencing error (see Supporting Information).…”
Section: Sequence Analysismentioning
confidence: 99%
“…이 중 맥크롤 라이드 계열 메티마이신 (S. venezuelae)의 DesVII/DesVIII 와 안쓰라사이클린 계열 엘로라마이신 (S. olivaceus)의 UrdGT2 등에 대한 당화효소의 역할과 기능의 다양성에 대하 여 보고되었다 (Fig. 5) [26][27][28]. 또한 새로운 당화효소의 확보 차원에서 Bechthold 그룹은 당화효소의 도메인 유사성 부분 에서 hybrid oligonucleotide 프라이머를 이용한 polymerase chain reaction (PCR) 방법을 이용하여 여러 actinomycetes 로부터 22개의 신규 당화효소를 분리하는데 성공하기도 하 였다 [29].…”
Section: 생물학적 유연성을 지닌 당화효소unclassified
“…These results revealed that UrdGT2 could both transfer different deoxysugars ( Dolivose or D -mycarose) and also use different acceptor substrates (the urdamycin or the premithramycin aglycones). Furthermore, UrdGT2 is able to catalyze both C -and O -glycosidic sugar transfers to the same aglycone [Durr et al, 2004], and to transfer in an unselective manner, both stereoisomers of rhodinose to the same position of urdamycin aglycone [Hoffmeister et al, 2003].…”
Section: Sugar Substrate Flexibility Of Glycosyltransferasesmentioning
confidence: 99%